THE INFLUENCE OF USING AUDIOVISUAL MEDIA AND LEARNING MOTIVATION OF CHILDREN STORIES WRITING ABILITY - Salwaa Nadiya Alif; St. Y. Slamet; Yulianti Yulianti (Universitas Sebelas Maret, 2018)
The purpose of this research is to find out : (1) the different of writing children stories ability of students that teached by audiovisual media within audio media, (2) the different of writing children stories ablility of students that have the high learning motivationand low learning motivation, (3) the interaction between teaching media and learning motivation on the writing children stories ability. This research includes a Quasi Experimental methode design by 2 × 2 factorial design. Populaton of the research are all students at fourth grade elementary school in Laweyan district Surakarta in the academic year of 2017/2018. The selected sample are Bratan III No. 187 Elementary School and Karangasem II Elementary School. This research used Two Ways Anava data analysis technique. The result of this research are : (1) there is different of writing children stories ability of students that teached by audiovisual media within audio media with FA value = 15,70 > F0,05;1;63 = 3,481; (2) there is different of writing children stories ablility of students that have the high learning motivationand low learning motivation with FB value = 3,80 > F0,05;1;63 = 3,481; (3) there is no interaction between teaching media and learning motivation on the writing children stories ability with FAB value = -0,10 < F0,05;1;63 = 3,481.